Parliament and Opinion (1688-1832) - Cannon, John (Czasopismo Prawno-Historyczne, 1989)
The subject suggested by the National Committee for this conference — Parliamentarism and Society — strikes me as interesting, important, and — certainly on the British side — potentially rather difficult. The eighteenth century — by which, with the usual licence, I mean 1688 to 1832 — used to have the reputation of an historical desert, where prowled savage and ferocious beasts and travellers were wise not to loiter. Among the more formidable beasts was Lewis Namier, who united in his person Poland and England. It has now blossomed in the most remarkable way. Revisionists cluster so thick round most subjects that they elbow each other aside and new revisionism in soon old establishment.